O‘ZBEKISTON VA HINDISTON MAMLAKAT XALQLARINING SPORT SOHASIDAGI MUNOSABATLARI - ASADOVA RA`NO BAYMANOVNA; Maxmudov Beкzod Eshqobil o`g`li (Лучшие интеллектуальные исследования, 2024)
Annotation: This article speaks of cooperation between Uzbekistan and India in the cultural field, identifying the main trends and prospects for further mutual cooperation.